Developing Students’ Creative and Entrepreneurial Skills via Project-based STEM Physics - Sartika, Vera; Halim, Abdul; Zainuddin, Zainuddin; Saminan, Saminan; Syukri, Muhammad (Heca Sentra Analitika, 2025)
Physics is a complex subject and requires a high level of understanding. Based on interviews at SMAN 4 Langsa, there has never been a test of creative thinking skills, there has been no learning that develops these skills, and students have a low entrepreneurial spirit. This study aims to improve physics learning through the PjBL-STEM (Project-Based Learning-Science, Technology, Engineering, and Mathematics) model, in improving students' creative thinking skills and entrepreneurial spirit. The research design used in this study was a one-group pretest-posttest design involving 89 grade X students. Data collection was conducted through interviews, questionnaires, and tests developed based on indicators of creative thinking skills. The data were analysed using the percentage formula, N-gain, Normality, and Paired Sample t-test. The instruments used were the Creative Thinking Skills Test and the Entrepreneurship Questionnaire. The results showed that the average N-gain of 0.71 was categorised as high. Based on the N-gain results, it can be concluded that there is an increase between before and after treatment. The results of the entrepreneurship questionnaire showed 45% before treatment and 82% after treatment. From the results of this study, it can be concluded that the PjBL-STEM model can optimise physics learning by improving students' creative thinking skills and entrepreneurial spirit.